A technique for studying the response of materials to high rate, high strain deformation - Winter, RE; Stirk, SM; Harris, EJ; Eakins, DE; Chapman, DJ (Elsevier, 2016)
A gas-gun technique is described in which a thick-walled cylinder of a chosen solid may be collapsed over a wide range of effective strains, and at shear strain-rates of the order 104 s−1. Two variants of the basic concept are described. Initially a 70 mm bore gun was used to dynamically collapse stainless steel 304 cylinders to a wide range of final effective strains. Early-stage shear bands were observed to intersect the inner circumference of the collapsed cylinder. However, although the configuration provides a useful vehicle for studying high rate, high strain deformation it has the disadvantage that the strain vs. time field experienced by the sample is complex. In addition, the 70 mm bore size limited the diameter of the specimen tube studied and hence diagnostic access to the collapsing cylinder wall was not possible. Therefore the Sandia hydrocode CTH was used to modify the initial configuration to generate a simpler strain history in the sample. This refinement of the original concept was used to implode cylinders of the titanium alloy Ti–6Al–4V using a larger 100 mm bore gas launcher. The velocities of the inner surfaces of the imploding cylinders were measured using optical velocimetry from which the macroscopic strain and shear strain-rate were determined as a function of time. The samples were sectioned after the tests, revealing severe localised adiabatic shear patterns. The gas-gun technique is shown to be a versatile configuration with potential for easily varying the specimen's initial geometry and the strain-rates at which it is collapsed.